Effective induction motor controller based Voltage/frequency - Liu, J.; Mekhilef, Saad; Li, H. (2011)
An effective scheme of induction motor control without using stator sensor is proposed in this paper. The effective scheme consist of speed calculation algorithm and voltage/frequency control. The speed calculation algorithm is achieved by sensoring the current of stator and compared with the prospective speed then calculation by DSP. The principles of constant voltage/frequency (V/Hz) control for AC Induction motor and sine wave generation of PWM technique are used. The control system has been tested at the real time operating conditions and the experimental results have shown that the system has good characteristic in steady state and during transient as well.